Profil Penggunaan Antibiotik yang Aman dan Rasional pada Pengobatan Penyakit Infeksi Gigi di Tempat Praktek Dokter Gigi Kota Bandung - Sheril Sisilia; Rida Emelia (Publikasi Indonesia, 2022)
Antibiotics should be used according to the regimen prescribed by a doctor or pharmacist to prevent resistance. Patients after an outpatient clinic may have problems with adherence to antibiotics. This study aims to understand the safe and rational use of antibiotics in the treatment of dental infectious diseases at a dentist's office in Bandung. Collecting data using a retrospective approach based on the order in which the patient took antibiotics and then classified according to the type, class, dose and duration of antibiotic administration. There are three types of antibiotics used, namely amoxicillin, cefixime, and lincomycin. The antibiotics used were in 3 groups, namely penicillins, gene-III cephalosporins, and other antibiotics. The most common dose of the antibiotic amoxicillin is 500 mg up to 3 times a day. The results showed the use of 3 antibiotics, namely amoxicillin, cefixime and lincomycin.